Analysis of User Experience and Perceived Value as the Basis for Enhancing User Loyalty Through User Satisfaction among Skill Academy Users in Jakarta, Indonesia - Mokhamad Wildan Marzuqon; Putu Nina Madiawati; Yogi Suprayogi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the influence of Perceived Value (PV) and User Experience (UE) on User Loyalty (UL), mediated by User Satisfaction (US), within the competitive Jakarta MOOC market. Utilizing PLS-SEM on cross-sectional data from 150 Skill Academy users, the research tested the structural model. The results confirm that PV and UE significantly and positively affect UL via direct effects, with PV being the strongest predictor. Crucially, the study finds that User Satisfaction does not significantly predict or mediate loyalty, confirming a breakdown in the affective chain and highlighting the dominance of calculative commitment in this sector. This research contributes by challenging the traditional assumption that satisfaction precedes loyalty in utilitarian digital environments. The implication is that retention strategies must prioritize maximizing utilitarian value and technical functionality, rather than subjective contentment.